2019
DOI: 10.1111/exd.13840
|View full text |Cite
|
Sign up to set email alerts
|

The absence of Rab27a accelerates the degradation of Melanophilin

Abstract: Melanophilin (Mlph) forms an interaction with Rab27a and the actin‐based motor protein MyosinVa (MyoVa) on mature melanosome membranes and the tripartite complex regulates melanosome transport in melanocytes. In this study, we found that Rab27a siRNA decreased Mlph and Rab27a protein levels, but Mlph mRNA levels were not changed. Other Rab27a siRNA sequences also showed the same results. When Rab27a siRNA was treated with melan‐a melanocytes, Rab27a protein was decreased within 6 hours and Mlph protein was dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Under physiological conditions, however, it is unclear whether EPI64/TBC1D10A is required for cargo (i.e., melanosome) unloading after actin‐dependent melanosome transport mediated by the Rab27A–Mlph/Slac2‐a–myosin Va tripartite complex. Since Mlph/Slac2‐a contains multiple PEST sequences that are highly sensitive to proteases and it undergoes proteasome‐mediated degradation, degradation of Mlph/Slac2‐a may result in disassembly of the tripartite protein complex and cargo unloading (Fukuda & Itoh, 2004; Park et al., 2019).…”
Section: Rab Gtpases In Melanosome Transport In Melanocytesmentioning
confidence: 99%
“…Under physiological conditions, however, it is unclear whether EPI64/TBC1D10A is required for cargo (i.e., melanosome) unloading after actin‐dependent melanosome transport mediated by the Rab27A–Mlph/Slac2‐a–myosin Va tripartite complex. Since Mlph/Slac2‐a contains multiple PEST sequences that are highly sensitive to proteases and it undergoes proteasome‐mediated degradation, degradation of Mlph/Slac2‐a may result in disassembly of the tripartite protein complex and cargo unloading (Fukuda & Itoh, 2004; Park et al., 2019).…”
Section: Rab Gtpases In Melanosome Transport In Melanocytesmentioning
confidence: 99%
“…A similar phenotype was observed in a recent study, where the knockdown of KIBRA, an adaptor protein for Rab27a, lead to the reduction in Rab27a protein expression (Song et al, 2019), as KIBRA interacts with Rab27a, stabilizing the protein and preventing its degradation via the ubiquitin-proteasome pathway. Another study demonstrated that Rab27a knockdown in melanocytes led to reduced levels of the effector protein Melanophilin due to an increase in proteasomal degradation (Park et al, 2019). This has also been in shown in vivo using Rab27a-deficient mice (Wu et al, 2002), suggesting that the interactions between Rab27 isoforms and their effectors are essential to the stability of each other.…”
Section: Discussionmentioning
confidence: 77%
“…It may play a significant role in both intestine and inner ear biology ( Choi et al, 2020 ; Kapustina and Cheney, 2020 ). We speculated that CALML4 maybe need combined with other melanin-related proteins to form a complex that participates in melanin production, similar to how melanophilin requires binding with Rab27a and myosin Va to affect melanosomes transport ( Park et al, 2019 ). And we found 2 potential candidate genes ( KITLG and EDNRB ) in female chicken, which could help us exhaustive understand the mechanisms of melanin production.…”
Section: Discussionmentioning
confidence: 99%